Pengaruh Likuiditas Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Tekstil Dan Garmen Yang Terdaftar Di Bursa Efek Indonesia - Solma, Solma; Usdeldi, Usdeldi; Diwantara, Victor (STAI Denpasar Bali, 2023)
The background of this research is the inconsistency in previous research which has different research results. The purpose of this study, in addition to strengthening previous research, is also to determine the effect of Liquidity (Current Ratio and Quick Ratio) on Profitability (Return On Assets) in Textile and Garment Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange with a research period of 6 years, from 2016-2021. The population in this study is 22 companies which are included in the Textile and Garment Sub Sector Manufacturing companies which are listed on the Indonesia Stock Exchange for the 2016-2021 period. The sample selection technique used in this study was a purposive sampling method using certain criteria and assessments in order to obtain a sample of 5 companies. In this study, the data analysis method used includes descriptive analysis, panel data regression test and model testing. Data were obtained from financial reports taken on the idx.co.id website or the company's website, then processed using Eviews 12. The results of this study partially show that Current Ratio (CR) has a significant and significant effect on Return On Assets (ROA), Quick Ratio has no effect and is not significant to Return On Assets (ROA). Meanwhile, simultaneously Current Ratio (CR) and Quick Ratio (QR) have a significant effect on Return On Assets (ROA).